1968
DOI: 10.1016/0041-008x(68)90105-1
|View full text |Cite
|
Sign up to set email alerts
|

The chick embryo test as used in the study of the toxicity of certain dithiocarbamates

Abstract: The Chick Embryo Test As Used in the Study of the Toxicity of Certain Dithiocarbamates. GEBHARDT, D. 0. E., and VAN LOGTEN, M. J. (1968). Toxicol. Appl. Pharmacol. 13, 316-324. The toxicities of six dithiocarbamates: bis(dimethy1 thiocarbamoyl) disulfide (thiram), zinc dimethyldithiocarbamate (ziram), ferric dimethyldithiocarbamate (ferbam), bis(dimethyl thiocarbamoyl) ethylene bis(dithiocarbamate) (triaram), sodium diethyl dithiocarbamate (NaDEDC), and sodium ethylene bis(dithiocarbamate) (nabam) were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The relationship between injection location and toxicity is unclear and inconsistent among chemicals. For example, 2,3,7,8‐tetrachloro‐ p ‐dibenzodioxin administered through the yolk in chicken eggs was more toxic relative to an air cell injection (LD50 = 122 vs 297 pg/g; Henshel et al ), but thiram exposure through the air cell was more toxic than through the yolk (LD50 = 1.1 vs 18 µg; Gebhardt and van Logten ). These results reiterate the importance of a standardized method for egg injections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between injection location and toxicity is unclear and inconsistent among chemicals. For example, 2,3,7,8‐tetrachloro‐ p ‐dibenzodioxin administered through the yolk in chicken eggs was more toxic relative to an air cell injection (LD50 = 122 vs 297 pg/g; Henshel et al ), but thiram exposure through the air cell was more toxic than through the yolk (LD50 = 1.1 vs 18 µg; Gebhardt and van Logten ). These results reiterate the importance of a standardized method for egg injections.…”
Section: Resultsmentioning
confidence: 99%
“…Eggs are most commonly injected prior to incubation (ED0) or on ED3 to 4. Gebhardt and Van Logten (1968) showed that the early embryo was sensitive to mechanical manipulations into the yolk; needle insertion alone caused 55% mortality on ED0 but only 5% mortality when performed on ED4. Air cell injection, on the other hand, had minimal effects on survival from ED0 to 4 (Gebhardt and Van Logten 1968).…”
Section: Timing Of Injection and Terminationmentioning
confidence: 99%
“…Our observation that the chick embryos were more sensitive to TCDD injected into the yolk rather than into the air cell is especially interesting in view of conclusions about the relative behavior and toxicity of yolk‐ versus air‐cell‐injected compounds made by Gebhardt and van Logten [22] and Gebhardt [23] and Walker [24]. Walker injected a number of dye‐labeled chemicals into the yolks of fertile chicken eggs and observed the behavior of the chemicals in the yolks.…”
Section: Discussionmentioning
confidence: 99%
“…Gebhardt and van Logten [22] applied thiram, a dithiocar‐bamate, dissolved in propylene glycol into the yolk and into the air cell of embryonic day one chicks. He reported that for these toxicants, the embryos were more sensitive to the thiram injected into the air cell (LD50 =1.1 μg), rather than into the yolk (LD50 = 18 μg).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the yolk sac, tecoram was also injected into the air chamber, as it was shown by Gebhardt and van Logten (1968), that certain dithiocarbamates were more effective, at least in the very young chick embryo, when this method of inoculation was used.…”
mentioning
confidence: 99%